Primary Zonal High Intensity Focused Ultrasound for Prostate Cancer: Results of a Prospective Phase IIa Feasibility Study. (23rd January 2014) - Van Velthoven, Roland; Aoun, Fouad; Limani, Ksenija; Narahari, Krishna; Lemort, Marc; Peltier, Alexandre
Abstract : Aims. In this study we report our results with storage of cryopreserved semen intended for preservation and subsequent infertility treatment in men with testicular cancer during the last 18 years. Methods. Cryopreserved semen of 523 men with testicular cancer was collected between October 1995 and the end of December 2012. Semen of 34 men (6.5%) was used for fertilization of their partners. They underwent 57 treatment cycles with cryopreserved, fresh, and/or donor sperm. Results. A total of 557 men have decided to freeze their semen before cancer treatment. Seminoma was diagnosed in 283 men (54.1%) and nonseminomatous germ cell tumors in 240 men (45.9%). 34 patients who returned for infertility treatment underwent 46 treatment cycles with cryopreserved sperm. Totally 16 pregnancies were achieved, that is, 34.8% pregnancy rate. Conclusion. The testicular cancer survivors have a good chance of fathering a child by using sperm cryopreserved prior to the oncology treatment, even when it contains only limited number of spermatozoa. Erratum to "Primary Zonal High Intensity Focused Ultrasound for Prostate Cancer: Results of a Prospective Phase IIa Feasibility Study" dx.doi.org/10.1155/2014/640859